2002
DOI: 10.1210/jcem.87.1.8148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treatment with GH Alone or in Combination with LHRH Analog on Bone Mineral Density in Pubertal GH-Deficient Patients

Abstract: The aim of the present study was to assess the impact of treatment with GH with or without LHRH analog (LHRH-A) on bone mineralization of GH-deficient adolescents. We studied 17 pubertal, treatment-naive, GH-deficient patients (10 girls and 7 boys) in a prospective, randomized trial. Mean chronological age and mean bone age were 14.1 +/- 0.4 and 11.3 +/- 0.3 yr, respectively, at the beginning of the study. Treatment with GH + LHRH-A (n = 7) or GH alone (n = 10) started simultaneously. Nutropin was administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…[117][118][119] Three prospective studies that reported near-AH or AH have shown an ϳ1-SD height gain, [120][121][122] possibly without detrimental effect on BMD. 123 Conclusions: Routine use of combined therapy with GnRH and GH in GH-deficient children with low predicted AH at onset of puberty cannot be suggested (CIII).…”
Section: Increasing Ah Of Children With Gh Deficiencymentioning
confidence: 99%
“…[117][118][119] Three prospective studies that reported near-AH or AH have shown an ϳ1-SD height gain, [120][121][122] possibly without detrimental effect on BMD. 123 Conclusions: Routine use of combined therapy with GnRH and GH in GH-deficient children with low predicted AH at onset of puberty cannot be suggested (CIII).…”
Section: Increasing Ah Of Children With Gh Deficiencymentioning
confidence: 99%
“…Osteoporosis is associated with many primary and secondary paediatric diseases 16 , 17 . Studies have shown that low BMD during adolescence can result in permanent low BMD in adulthood 18 . The vital period for the growth and development of children is between zero and 3 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with central precocious puberty or GH-deficient children who are diagnosed late in childhood often have a decreased height potential, and a strategy to increase their adult height is to use GnRH analogues or add GnRH analogues to the GH treatment regimen, thereby delaying puberty and slowing skeletal maturation. These treatments raise concern that the suppression of puberty with GnRH analogues might have an adverse effect on bone mineral acquisition during puberty, although this strategy has recently been demonstrated to have no adverse effect on bone mineralization (9,10,11). From our observations, however, we propose that the build-up of bone mass in boys as a result of the effects of testosterone should not be neglected, and this issue remains to be further clarified.…”
Section: Commentsmentioning
confidence: 99%